2022
DOI: 10.1186/s12883-022-02549-w
|View full text |Cite
|
Sign up to set email alerts
|

One-year outcome of brain injured patients undergoing early neurological rehabilitation: a prospective observational study

Abstract: Background The present study intended to analyze the outcome of patients with severe brain injury one-year after discharge from early rehabilitation. Methods Early neurological rehabilitation patients admitted to intensive or intermediate care units and discharged between June 2018 and May 2020 were screened for eligibility. The level of consciousness was evaluated using the Coma Recovery Scale-Revised (CRS-R) upon admission and at discharge. At on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Some recent large-scale clinical trials and a meta-analysis concluded that younger patients recover more frequently. 6,17,31,32 We were unable to confirm this Cumulative incidence (%) finding in the overall sample. However, our additional analysis revealed that older patients die earlier and more frequently than younger patients.…”
Section: Discussionmentioning
confidence: 61%
“…Some recent large-scale clinical trials and a meta-analysis concluded that younger patients recover more frequently. 6,17,31,32 We were unable to confirm this Cumulative incidence (%) finding in the overall sample. However, our additional analysis revealed that older patients die earlier and more frequently than younger patients.…”
Section: Discussionmentioning
confidence: 61%
“…At the end of early rehabilitation, the length of stay and the type of discharge (e.g., nursing care, returning home) were determined. Finally, the Glasgow Outcome Scale-extended (GOSE) was assessed 1 year after discharge from early rehabilitation via telephone interviews (for further details, see [ 9 ]).…”
Section: Methodsmentioning
confidence: 99%
“…Their result showed those patients who had MCS (Minimally Conscious State) upon admission showed a better outcome after discharge and were more likely to recover within one-year post-injury in terms of their level of consciousness, unlike the patients who suffered UWS (Unresponsive Wakefulness Syndrome) since Day 1 of admission. (10) Data on the effect of neurorehabilitation on the degree of level of consciousness in patients experiencing brain-related injuries remains largely unexplored and is still under study.…”
Section: Association Between Neuro-rehabilitation and Changes In Leve...mentioning
confidence: 99%